Effect of Carcinoembryonic Antigen-related Cell Adhesion Molecule-binding Recombinant Polypeptide on the Killing of Neisseria meningitidis by Human Neutrophils - Abdel-Rahman Youssef (Journal of Umm Al-Qura University for Medical Science, 2021)
Background: Neutrophils are an essential part of innate immunity and play a crucial role in controlling infection caused by Neisseria meningitidis. The Moraxella catarrhalis ubiquitous surface protein A1 (UspA1)-based recombinant polypeptide binds to the carcinoembryonic antigen-related cellular adhesion molecule (CEACAM) 1 receptor on host cells and blocks binding of the mucosal pathogens to human epithelial cells and T cells. Aim of the study: Since the CEACAM1 receptor is expressed on neutrophils, the aim of this study was to investigate the effect of CEACAM1-binding recombinant polypeptide on the ability of neutrophils to kill Neisseria meningitidis. Methods: The effect of CEACAM1-binding recombinant polypeptide on the phagocytic killing of Neisseria meningitidis by neutrophils was assessed by incubation of neutrophils with CEACAM1-binding recombinant polypeptide (UspA1 527–665) or with CEACAM1-non-binding polypeptide control (UspA1 659–863) for one hour before infection with Neisseria meningitidis. The surviving bacteria were released and counted. Results: 30 minutes after infection of neutrophils with Neisseria meningitidis, the survival of bacteria in presence of CEACAM1-binding recombinant polypeptide was 64% compared to 52% with control peptide and 43% without peptide. However, one-hour after infection, the surviving bacteria was 32% in presence of CEACAM1-binding recombinant polypeptide compared to 18% with control peptide and 22% without peptides. Conclusion: Although CEACAM1-binding polypeptide reduced the killing of Neisseria meningitidis by neutrophils, it did not entirely stop phagocytosis and killing of bacteria.